Trunk muscle strength and disability level of low back pain in collegiate wrestle - Iwai, K.; Nakazato, K.; Irie, K.; Fujimoto, H.; Nakajima, H. (Medicine & Science in Sports & Exercise, 2004)
INTRODUCTION/PURPOSE: Low back pain (LBP) is a frequent injury in athletes. This study examined the relationship between isokinetic trunk muscle strength and the functional disability level of chronic LBP. We particularly focused on the existence of radiological abnormalities (RA) in the lumbar region. METHODS: Subjects were 53 collegiate wrestlers. Trunk extensor and flexor muscle strength was measured at three angular velocities (60, 90, and 120degrees x s(-1)). The examined parameters for trunk muscle strength were peak torque, work, average torque, and average power. The disability level of LBP was estimated by using two questionnaires. Based on the RA evaluation with x-ray and MRI, all 53 wrestlers were assigned to two groups as the RA group (N = 35, 66%) and the non-RA group (N = 18, 34%). Correlations between trunk muscle strength and the disability level of LBP in each group were analyzed with Spearman's rank test. RESULTS: Without considering the disability level, there were 14 subjects with LBP (40%) in the RA group and 8 (44%) in the non-RA. Significantly correlated parameters with the disability level of LBP could be observed only when the subjects were restricted to the non-RA group. The correlated parameters with the two questionnaires were peak torque at 120degrees x s(-1), work at 60degrees x s(-1) and 90degrees x s(-1), and average torque at 90degrees x s(-1) and 120degrees x s(-1). There were no significantly correlated parameters in the RA group. None of the trunk flexor parameters were significantly correlated with the disability level of LBP. CONCLUSION: The relatively low strength of trunk extensors may be one of the factors related to nonspecific chronic low back pain in collegiate wrestlers.